Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/gtc.12448
|View full text |Cite
|
Sign up to set email alerts
|

Small spheroids of adipose‐derived stem cells with time‐dependent enhancement of IL‐8 and VEGF‐A secretion

Abstract: Wound-healing factors secreted from mesenchymal stem cells (MSCs) modulate the immune response and facilitate proliferation of neighboring cells. Although in vitro three-dimensional (3D) culture techniques have improved the therapeutic potential of MSCs, no studies have focused on the effects of cell aggregation alone. In this study, the effect of cell aggregation on the up-regulation of wound-healing proteins secretions was investigated by constructing small spheroids of human adipose-derived stem cells (hADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The characteristics of rat ADMSCs (Figure S1A, Supporting Information) were analyzed by flow cytometry analysis using MSC surface markers, CD90, and CD29 (Figure S1B, Supporting Information). To generate injectable spheroids, MSCs were cultured in nonadhesive micropatterned plates . The culture allowed for the rapid generation of spheroids without the labor‐consuming work of the conventional hanging drop method .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of rat ADMSCs (Figure S1A, Supporting Information) were analyzed by flow cytometry analysis using MSC surface markers, CD90, and CD29 (Figure S1B, Supporting Information). To generate injectable spheroids, MSCs were cultured in nonadhesive micropatterned plates . The culture allowed for the rapid generation of spheroids without the labor‐consuming work of the conventional hanging drop method .…”
Section: Resultsmentioning
confidence: 99%
“…Spheroids of this size are intra-articularly injectable and avoid hypoxic and necrotic side effects that occur in the core of large spheroids. [17] The number of cells in each spheroid did not changed during spheroid formation. The histological and bright-field images of the spheroids used in this study are shown in Figure 2A and Figure S2B (Supporting Information), respectively.…”
Section: Characterization Of Mscs and Spheroidsmentioning
confidence: 92%
See 1 more Smart Citation
“…IL-8 was reported as being a pro-inflammatory interleukin with pro-angiogenic properties (Hou et al 2014). Untreated or unstimulated ASC has the capacity to secrete IL-8 (Silva et al 2015), which contributes to their regenerative capacity (Furuhata et al 2016). The effects of Ag nanoparticles in cytokines secretion are complex and controversial depending on cell and tissue types (Shin et al 2007, Nishanth et al 2011, besides physio- (Hackenberg et al 2011) and pathological scenarios (Silva et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MSC spheroid formation have reported and changes in the secretion level of wound-healing related proteins. 443 Compared with MSC cultured monolayer, the spheroid formation on microdomain up-regulated the secretion level of these proteins. In the case of MSC, effective reduction of differentiation induction time for osteoblast cells was accomplished using microdomain patterned surface, where cell accumulations accelerate the osteogenic differentiation in gene expression level (Figure 31).…”
Section: Biointerfaces Constructed By Top Down Approachesmentioning
confidence: 96%